Pentateuch, Hexateuch, or Enneateuch?: identifying literary works in Genesis through Kings - Dozeman, Thomas B.; Römer, Thomas; Schmid, Konrad (Ancient Israel and its literature, 2012)
The emergence and disappearance of the separation between the Pentateuch and the deuteronomistic history in biblical studies / Thomas Römer -- How many books (teuchs) : Pentateuch, Hexateuch, Deuteronomistic History, or Enneateuch? / Erhard Blum -- Pentateuch-Hexateuch-Enneateuch, or, How can one recognize a literary work in the Hebrew Bible? / David M. Carr -- "Empircal" comparison and the analysis of the relationship of the Pentateuch and the former prophets / Suzanne Boorer -- The envisioning of the land in the priestly material : fulfilled promise or future hope? / Christoph Levin -- On the cohesion and separation of books within the Enneateuch / Cynthia Edenburg -- From Eden to Babylon : reading Gen. 2-4 as a paradigmatic narrative / Michael Konkel -- Exodus 32 / Thomas Dozeman -- The Book of Joshua as an intertext in the MT and the LXX canons / Christoph Berner -- The Egyptian bondage and Solomon's forced labor : literary connections between Exod. 1-15 and 1 Kgs. 1-12? / Felipe Blanco Wissmann -- "He did what was right" : criteria of judgment and Deuteronomism in the books of Kings